Boundaries of oral genres: strange case of rhetorical toast and lyrical praise poem - Nikolić, Davor (Poznańskie Studia Slawistyczne, 2025)
The paper discusses boundaries between the toast as an oral rhetorical genre and the praise poem as an oral lyrical genre. While on the one hand a toast (as a hybrid rhetorical genre) is related to a blessing (a primary rhetorical genre), on the other it is compared to the praise poem, with which it shares many structural and performative elements. The main segment of the paper is focused on establishing principal rhetorical traits and comparing some prototypical examples of both genres.